2016
DOI: 10.1111/joim.12575
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor – HPV vaccine and autoimmunity Incidence of new‐onset autoimmune disease in girls and women with pre‐existing autoimmune disease after quadrivalent human papillomavirus vaccination: a cohort study

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/joim.12574/abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…81,82 Whereas some studies present no association between HPV vaccines and autoimmune adverse events, [83][84][85][86] others have addressed the significant limitations of many of these analyses. 87,88 The answer remains largely disputed, yet the attention drawn to HPV may be responsible for some intriguing discoveries regarding potential molecular mimicry between HPV and human proteins. In two comprehensive analyses Kanduc et al 9,89 exposes vast peptide overlap between peptides of HPV to the human proteome, 90 thus laying the grounds for further research regarding HPV and autoimmunity.…”
Section: Human Papilloma Virus Vaccines: a Veil Of Concern Remains Unmentioning
confidence: 99%
“…81,82 Whereas some studies present no association between HPV vaccines and autoimmune adverse events, [83][84][85][86] others have addressed the significant limitations of many of these analyses. 87,88 The answer remains largely disputed, yet the attention drawn to HPV may be responsible for some intriguing discoveries regarding potential molecular mimicry between HPV and human proteins. In two comprehensive analyses Kanduc et al 9,89 exposes vast peptide overlap between peptides of HPV to the human proteome, 90 thus laying the grounds for further research regarding HPV and autoimmunity.…”
Section: Human Papilloma Virus Vaccines: a Veil Of Concern Remains Unmentioning
confidence: 99%
“…We read the recent correspondence by Drs Dahan and Shoenfeld [1] with confusion and concern. A response by Gronlund et al [2] very adroitly addressed several of the concerns of Dahan and Shoenfeld by undertaking re-analysis of their data.…”
Section: Dear Sirmentioning
confidence: 99%
“…15,16 In contrast, HPV vaccination significantly reduced the prevalence of RA in adults aged 18 to 59 years. 12 Because of the amino acid sequence similarity between HPV antigen and numerous human proteins, 17,18 HPV-47 E2345-362 peptide has homology with the epitope of RA autoantigen; thus, HPV-induced autoantibodies against viral antigen promoted pathogenesis of RA. 12 An observational study found that 33% of patients with RA had HSV I and HSV II DNA in both their blood and synovial fluid samples.…”
mentioning
confidence: 99%